2017
DOI: 10.1212/wnl.0000000000003537
|View full text |Cite
|
Sign up to set email alerts
|

Long-term cortisol measures predict Alzheimer disease risk

Abstract: Objective: To examine whether long-term measures of cortisol predict Alzheimer disease (AD) risk.Method: We used a prospective longitudinal design to examine whether cortisol dysregulation was related to AD risk. Participants were from the Baltimore Longitudinal Study of Aging (BLSA) and submitted multiple 24-hour urine samples over an average interval of 10.56 years. Urinary free cortisol (UFC) and creatinine (Cr) were measured, and a UFC/Cr ratio was calculated to standardize UFC. To measure cortisol regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(80 citation statements)
references
References 39 publications
4
76
0
Order By: Relevance
“…This is supported by the evidence that increased plasma levels have been reported in the early stages of AD patients [19, 20] and decreased sensitivity to low-dose dexamethasone suppression [6]. Similarly, patients with sporadic AD have increased plasma cortisol levels during the onset and later stages [21-23]. Another study reported that elevated basal cortisol levels and the severity of cognitive deficits in AD patients have been correlated with increased 24-h cortisol levels [24].…”
Section: Endocrinal Dysregulations In the Ad Pathophysiologymentioning
confidence: 75%
“…This is supported by the evidence that increased plasma levels have been reported in the early stages of AD patients [19, 20] and decreased sensitivity to low-dose dexamethasone suppression [6]. Similarly, patients with sporadic AD have increased plasma cortisol levels during the onset and later stages [21-23]. Another study reported that elevated basal cortisol levels and the severity of cognitive deficits in AD patients have been correlated with increased 24-h cortisol levels [24].…”
Section: Endocrinal Dysregulations In the Ad Pathophysiologymentioning
confidence: 75%
“…While there are relatively few studies of similar size for comparison, our finding that HPAA dysfunction is associated with later-life cognitive impairment is in keeping with findings of the Baltimore Longitudinal Study of Aging and the Longitudinal Aging Study of Amsterdam, which reported increased diurnal variation and random cortisol levels in similarly aged older adults to be associated prospectively with impaired cognitive function and Alzheimer disease risk, respectively. 11,27 In addition, HPAA dysfunction had also been previously associated with prospective cognitive decline in cognitively healthy adults with positive β-amyloid on PET scans, suggesting that HPAA dysfunction may be a marker of, share, or even mediate pathogenic β-amyloid mechanisms in cognitive impairment that may represent early preclinical phases of Alzheimer disease. 28 Our findings also suggest an association between HPAA dysfunction and cognition only becomes evident at older ages, 27 in keeping with a sensitive period for cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…45 Additionally, urinary free cortisol concentrations in the high-to-normal range are associated with an increased risk of Alzheimer’s disease. 46 Further, independent of disease, higher morning salivary cortisol concentrations in men and higher night salivary cortisol concentrations in women are associated with increased all-cause 6 to 7·5-year mortality. 47 …”
Section: Hypothalamic–pituitary–peripheral Organ Axesmentioning
confidence: 96%